The effect of involuntary retirement on healthcare use and health status - Anikó Bíró; Réka Branyiczki; Petér S. Elek (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
We analyse the causal effect of involuntary retirement on detailed indicators of healthcare use and health status. Our identification strategy is based on a pension reform in Hungary which forced public sector workers above the statutory retirement age to full time retirement. Using rich administrative data, we find that on the three-year horizon, involuntary retirement decreases the number of primary care doctor visits, the consumption of antiinfectives for systemic use and drugs of the respiratory system, and the non-zero spending on antiinfectives, the drugs of the alimentary tract and metabolism and of the cardiovascular system. We also find that the impact on the latter two drug categories is driven by the drop in income due to involuntary retirement. The effects of involuntary retirement are comparable to the short-run effects of voluntary retirement, identified from a change in the statutory retirement age. We conclude that there is little evidence for health deteriorating effects of involuntary retirement and provide explanations for the possible mechanisms behind our results.
Keywords: I10; J26; 330; healthcare use; involuntary retirement; voluntary retirement